2013
DOI: 10.3109/08923973.2013.811596
|View full text |Cite
|
Sign up to set email alerts
|

Acacetin inhibits expression of E-selectin on endothelial cells through regulation of the MAP kinase signaling pathway and activation of NF-κB

Abstract: Since E-selectin-mediated adhesion of leukocytes or tumor cells to the vascular endothelium is a key early event in the initiation of inflammatory response and cancer metastasis, E-selectin inhibition is thought to be a good target for therapeutic intervention. Several flavones have been shown to have anti-inflammatory and anticancer properties. In the present study, we investigated the effects of plant flavones on expression of E-selectin in human umbilical vein endothelial cells. Among 11 flavones, acacetin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…However, whether Acacetin has a direct blocking effect on CRAC channels, through which Ca 2+ entry mediates T cell activation, requires further investigation. Acacetin may also directly target the inflammation-related transcription factors [34] or the inflammatory intermediates iNOS and COX-2 [2]. Consistent with these findings, in animal models, Acacetin can ameliorate autoimmune delayed-type hypersensitivity and have no obvious side effects [3].…”
Section: Discussionsupporting
confidence: 58%
“…However, whether Acacetin has a direct blocking effect on CRAC channels, through which Ca 2+ entry mediates T cell activation, requires further investigation. Acacetin may also directly target the inflammation-related transcription factors [34] or the inflammatory intermediates iNOS and COX-2 [2]. Consistent with these findings, in animal models, Acacetin can ameliorate autoimmune delayed-type hypersensitivity and have no obvious side effects [3].…”
Section: Discussionsupporting
confidence: 58%
“…Endothelial cells are the target of inflammatory responses and thereby, of a number of severe disorders, including sepsis and multiple organ dysfunctions that occur via LPS stimulation (11). In this study, we detected the expression of the adhesion molecules, E-selectin and ICAM-1 in LPS-treated porcine iliac artery endothelial cells (PIECs), since the upregulation of adhesion molecules and the increased secretion of cytokines and chemokines are known to occur during endothelial cell activation (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells are the target of inflammatory responses and thereby, of a number of severe disorders, including sepsis and multiple organ dysfunctions that occur via LPS stimulation (11). In this study, we detected the expression of the adhesion molecules, E-selectin and ICAM-1 in LPS-treated porcine iliac artery endothelial cells (PIECs), since the upregulation of adhesion molecules and the increased secretion of cytokines and chemokines are known to occur during endothelial cell activation (12)(13)(14).The evolutionary conserved family of mitogen-activated protein kinases (MAPKs) includes extracellular p38 MAPK, extracellular regulated protein kinase (ERK) and c-Jun N-terminal kinase (JNK) (15). Numerous environmental stresses, such as osmotic shock, ultraviolet irradiation, as well as LPS and pro-inflammatory cytokines, have been confirmed to activate MAPK signaling cascades in a variety of cell lines (11,16).…”
mentioning
confidence: 99%
“…Acacetin (5,7-dihydroxy-40-methoxyflavone) is present in many plants such as thistle, safflower seed, acacia, induces apoptosis and has been reported anti-peroxidative, anti-inflammatory, anti-plasmodial and anti-proliferative effect by blocking cell cycle progression. [28][29][30][31][32][33] Several recent studies showed that acacetin to inhibit the proliferation of A549 cells lung cancer cells and HepG2 human liver cancer by blocking the cell cycle progression. 31,34 Acacetin inhibited the growth of human breast cancer MCF-7 cells and inhibits cell growth and cell cycle progression, and induces apoptosis in human prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%